Transition Of Digital Product Purchase Preferences: A Study Of Switching Intention From Physical Stores To Digital Marketplace In Indonesia - Siti Nasuha; Ponirin Ponirin; Umar Syarifuddin; Faruq Lamusa (UNIVED Press, 2025)
This study aims to examine the influence of push and pull factors on the switching intention in purchasing for digital products from physical stores to digital marketplaces, as well as to identify the moderating role of mooring factors in the relationship between push and pull factors and switching intention. A quantitative approach was employed, using purposive sampling and involving 179 respondents in Indonesia, analyzed through the PLS-SEM method. The results show that push factors, specifically consumer dissatisfaction, have a significant effect on switching intention. Additionally, pull factors, which include online service quality, perceived ease of use, and perceived of price, significantly influence the switching in purchasing intention. Mooring factors negatively moderate the relationship between pull factors and switching intention, thereby weakening consumers’ intention to switch despite attractive alternatives. However, mooring factors do not significantly moderate the relationship between push factors and switching intention. This study provides insights into consumer behavior dynamics in the channel transition from physical stores to digital marketplaces and offers strategies that businesses can implement to enhance the adoption of online digital product purchasing.